Formulasi dan Uji Stabilitas Fisik Sediaan Gel Ekstrak Daun Secang (Biancaea sappan L.) sebagai Obat Luka Bakar - Sawiji, Repining Tiyas; Kumanireng, Maria Ariyani Da Costa (Sainstech Farma: Jurnal Ilmu Kefarmasian, 2025)
Burns constitute damage to skin tissue caused by exposure to thermal, chemical, or electrical agents. The severity of burns can profoundly impact metabolic processes and cellular function. Although silver sulfadiazine is a common treatment, its prolonged use may induce skin irritation. Traditionally, secang leaves (Biancaea sappan L.) have demonstrated pharmacological effects that promote the accelerated healing of burn wounds. Given their flavonoid content, which is instrumental in stimulating wound healing, secang leaves hold promise for development into traditional medicinal preparations. Carbopol 940, a well-known gel-forming agent, is recognized for its influence on the physical properties of gel formulations. This study seeks to investigate the impact of different concentrations of Carbopol 940 on secang leaf extract gel preparations and to assess the physical stability of these gel formulations through the cycling test method. Secang leaf extract, used as an active ingredient, was formulated into three distinct gel preparations with varying concentrations of Carbopol 940 as a gelling agent: F1 (1%), FII (1.5%), and FIII (2%). The physical characteristics of these gel preparations were thoroughly tested, including organoleptic properties, homogeneity, pH, spreadability, stickiness, and viscosity. To assess stability, the gel preparations underwent a cycling test method, consisting of 6 cycles. Each cycle involved exposing the samples to a temperature of ± 4°C for 24 hours, followed by a hot temperature of ± 40°C for another 24 hours. The research findings indicate that variations in the concentration of Carbopol 940, along with the addition of TEA (Triethanolamine), significantly impacted the physical characteristics of the gel preparations. Specifically, an increase in Carbopol 940 concentration resulted in higher pH and viscosity, while spreadability and stickiness decreased. Based on these results, FIII (with 2% Carbopol 940) was concluded to meet the physical criteria for a secang leaf extract (Biancaea sappan L.) burn gel preparation. It exhibited a pH value of 6, a spread power of 5.5, an adhesion power of 1.38, and a viscosity of 275. Therefore, FIII is considered the most optimum gel formula.